Strategic Approaches to Managing Tantrum Behavior in Early Childhood Education Institutions - Nor Aishah Binti Adnan; Mangihut Siregar; Irlon Irlon; Muhammad Arib Sulaiman; Rizky Hasibuan; Riyadlotus Sholichah Riyadlotus Sholichah (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
There has been no comprehensive synthesis of strategies specifically designed for managing tantrum behaviour in early childhood within Early Childhood Education (ECE) settings. This study aims to analyse and explain various approaches used to handle tantrum behaviour in early childhood as implemented in ECE institutions. The research employs a Systematic Literature Review based on the Scopus database covering the period from 2016 to 2026, involving stages such as searching, selection, quality assessment, thematic analysis, synthesis of findings, and data interpretation related to tantrum management strategies in ECE. Results indicate that different tantrum management techniques in early childhood education settings are effective in reducing tantrum occurrences and enhancing children’s emotional regulation. Collaborative play activities contribute to improving social skills and cooperation among children. Mental health screening programmes support early detection of emotional and behavioural disorders. Social and Emotional Learning (SEL) programmes have been demonstrated to improve self-control, emotional management skills, and classroom engagement. Additionally, parent education, audio-visual affirmation therapy, and the use of wearable technology can significantly decrease the frequency and duration of tantrums in early childhood. Conclusion: Preventive, educational, collaborative, and technology-driven strategies are effective for reducing tantrum behaviour and fostering children’s socio-emotional development. Research significance: This study provides scientific references for teachers and researchers to design effective tantrum management strategies in early childhood education.